Stanniocalcin 1 is overexpressed in multipotent mesenchymal stromal cells from acute myeloid leukemia patients. Issue 1 (1st January 2021) - Schelker, Roland Christian; Kratzer, Andrea; Müller, Gunnar; Brochhausen, Christoph; Hart, Christina; Stempfl, Thomas; Heudobler, Daniel; Moehle, Christoph; Herr, Wolfgang; Iberl, Sabine; Grassinger, Jochen
ABSTRACT: Objectives: Multipotent mesenchymal stromal cells (MSC) play a pivotal role in the bone marrow (BM) niche. Stanniocalcin 1 (STC1) secreted by MSC has been demonstrated to promote the survival of neoplastic cells and was suggested a marker for minimal residual disease of acute myeloid leukemia (AML). Therefore, we evaluated the expression of STC1 in MSC from AML patients (MSCAML ) compared to MSC from healthy donors (MSCHD ). Methods: Liquid culture assays of MSCAML and MSCHD were performed to compare expansion capacity. Gene expression profiles of MSCAML vs. MSCHD were established. Secretion of STC1 was tested by ELISA in MSCAML vs. MSCHD and expression of STC1 in AML- vs. HD-BM by immunohistochemistry. In addition, co-cultures of AML cells on MSC were initiated and ultrastructural intercellular communication patterns were investigated. Finally, the effect of blocking STC1 on AML cells was evaluated. Results: MSCAML showed significant decreased expansion capacity compared to MSCHD . Gene analysis revealed marked overexpression of STC1 in MSCAML . ELISA and immunohistochemical findings confirmed this observation. Electron microscopy analysis showed reciprocal stimulation between AML cells and MSC. Blockade of STC1 did not significantly affect AML cell proliferation and apoptosis. Discussion: Characteristics of MSC differ depending on whether they originate from AML patients or from HD. STC1 was mostly overexpressed in MSCAML compared to MSCHD . In vitro blockade of STC1, however, was not associated with AML cell proliferation and apoptosis. Conclusion: Differences in expression levels of glycoproteins from MSCAML compared to MSCHD not necessarily assume that these molecules are niche-relevant in leukemic disease.